New method to synthesize mesoporous titania by photodegradation of surfactant template - Zi S.C.; Chandren S.; Yuan L.S.; Razali R.; Ho C.S.; Hartanto D.; Indra Mahlia T.M.; Nur H. (Elsevier Masson SAS, 2023)
Catalysts; Gas adsorption; High resolution transmission electron microscopy; Mesoporous materials; Photodegradation; Pore size; Styrene; Surface active agents; Titanium; Transmission electron microscopy; X ray diffraction; Cetyl trimethyl ammonium bromides; Diffuse reflectance; Fourier transform infrared spectra; Mesoporous titania; Nitrogen adsorption; Oxidation of styrene; Surfactant template; Ultra violet-visible; Titanium dioxide